2017
DOI: 10.1002/etc.3726
|View full text |Cite
|
Sign up to set email alerts
|

Temporal monitoring of perfluorooctane sulfonate accumulation in aquatic biota downstream of historical aqueous film forming foam use areas

Abstract: Perfluoroalkyl substances (PFAS) have recently received increased research attention, particularly concerning aquatic organisms and in regions of exposure to aqueous film forming foams (AFFFs). Air Force bases historically applied AFFFs in the interest of fire training exercises and have since expressed concern for PFAS contamination in biota from water bodies surrounding former fire training areas. Six PFAS were monitored, including perfluorooctane sulfonate (PFOS), in aquatic species from 8 bayou locations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 29 publications
1
51
0
Order By: Relevance
“…Lanza et al () and Lanza () report whole‐organism and tissue‐specific residue concentrations for PFASs in fish collected from Barksdale Air Force Base. These data were compared to tissue‐residue NOECs and LOECs from Wang et al (; whole organism) and Ankley et al (; liver tissue).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lanza et al () and Lanza () report whole‐organism and tissue‐specific residue concentrations for PFASs in fish collected from Barksdale Air Force Base. These data were compared to tissue‐residue NOECs and LOECs from Wang et al (; whole organism) and Ankley et al (; liver tissue).…”
Section: Resultsmentioning
confidence: 99%
“…Like many others, we used the lone standard USEPA method (537; Shoemaker et al ) available as the basis for analysis of surface water and sediment extracts, despite the method being limited to finished drinking water. For tissue samples, additional methods were developed, primarily quick, easy, cheap, effective, rugged, and safe–(QuEChERS) based tissue extractions (Lanza et al ; Karnjanapiboonwong et al ) prior to liquid chromatography–mass spectrometry analysis. We followed many of the quality assurance/control criteria described in USEPA Method 537 (for example, analytes within 70–130% of their true value for each calibration standard, initial calibration verification, continuing calibration verification ± 30% of true value, surrogates, internal standards, laboratory control samples, matrix spikes) in an effort to ensure data of the highest quality attainable.…”
Section: Methodsmentioning
confidence: 99%
“…As shown in Exhibit , three studies were identified (Awad et al., ; De Silva et al., ; Kannan et al., ) that contained whole body freshwater fish results for PFOS and PFOA, one additional site with results for just PFOA (DuPont, ), and two sites with results for just PFOS (although some other PFAS were also detected) (Lanza et al., ; OECD, ). Five results reported from the Great Lakes exhibited mean concentrations of PFOS ranging from 2.3 to 96 μg/kg ww, while two results from Canada exhibited concentrations ranging from 13.6 to 58 μg/kg ww.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Five results reported from the Great Lakes exhibited mean concentrations of PFOS ranging from 2.3 to 96 μg/kg ww, while two results from Canada exhibited concentrations ranging from 13.6 to 58 μg/kg ww. A recent study from Air Force Base (AFB; Bossier City, Louisiana) reports geometric mean whole fish homogenate PFOS background concentrations at 113 μg/kg dw (Lanza et al., ; ww whole fish homogenate data may reflect lower PFAS levels). Five results reported from the Great Lakes, plus one additional U.S. result, exhibited mean concentrations of PFOA ranging from <0.42 to 1.83 μg/kg ww, while the two results from Canada exhibited concentrations ranging from <0.1 to 0.4 μg/kg ww.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…; Lanza et al. ). In the United States, most Department of Defense facilities with aircraft runways are still required to keep and annually test PFAS‐containing AFFF foam for use on aircraft crashes (Kempisty et al.…”
Section: What Are Pfas and Where Are They Found?mentioning
confidence: 99%